(untitled) (Vietnam Journal of Community Medicine, 2026)
Introduction: Meibomian gland dysfunction (MGD) is the leading cause of dry eye disease due to abnormalities in the lipid layer of the tear film. Warm eyelid compress using the warm patch, inexpensive, and easily applicable treatment method. Aim of Study: To evaluate the efficacy of warm eyelid compresses in improving symptoms, clinical signs, and Meibomian gland function in patients with MGD. Methods: The study was conducted on 68 eyes of 34 patients diagnosed with MGD, treated with warm eyelid compresses for 8 weeks. Assessment parameters included the Ocular Surface Disease Index (OSDI), tear break-up time (TBUT). Results: The mean age was 56.8 ± 14 years. Females accounted for the majority with 91.2%. After intervention, patients reported reduced ocular discomfort. Mean OSDI scores decreased (47.63 ± 17.72; 38.88 ± 13.62; 33.89 ± 13.29), while TBUT increased (4.59 ± 3.51; 5.16 ± 2.2; 5.5 ± 2.3) at 4 and 8 weeks. No serious adverse effects were recorded. Conclusion: Warm eyelid compress is a safe, effective, and easy-to-apply method in the treatment of Meibomian gland dysfunction. The study results support its routine use as a fundamental therapeutic option for patients with MGD.